2011
DOI: 10.1002/ajim.20986
|View full text |Cite
|
Sign up to set email alerts
|

Coal dust exposure and mortality from ischemic heart disease among a cohort of U.S. coal miners

Abstract: There was an increased risk of mortality from IHD associated with cumulative exposure to coal dust, and with coal rank. The effect of coal rank may be due differences in the composition of coal mine dust particulate. The association of risk of IHD mortality with cumulative particulate exposure is consistent with air pollution studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 45 publications
0
45
0
3
Order By: Relevance
“…Exposure to different size fractions of particulate matter (PM) has adverse health effects on human health in environmental and occupational settings (Antonini 2003; Bhatti et al 2011; Landen et al 2011; Polichetti et al 2009; Samet and Krewski 2007). Particle deposition in the human respiratory tract and the consequent adverse health effects that may develop depends strongly on particle size (Brown et al 2002; Schwartz and Neas 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to different size fractions of particulate matter (PM) has adverse health effects on human health in environmental and occupational settings (Antonini 2003; Bhatti et al 2011; Landen et al 2011; Polichetti et al 2009; Samet and Krewski 2007). Particle deposition in the human respiratory tract and the consequent adverse health effects that may develop depends strongly on particle size (Brown et al 2002; Schwartz and Neas 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ultra-fine silica particles may cross the pulmonary epithelium into the vascular bed and directly affect the integrity of the vascular endothelium [9, 10]. Interestingly, cardiovascular diseases are among the leading causes of death in patients with silicosis [11]. …”
Section: Introductionmentioning
confidence: 99%
“…A cohort study of 74,040 workers reported that each 1 mg/m 3 increase in cumulative silica exposure was associated with a 3.1 % increase in the mortality for cardiovascular diseases . Several studies have also found that cardiovascular disease is the leading cause of death in silicosis patients of coal mines (Landen et al 2011;Morozova 2012). The positive relationship between occupational silica exposure and chronic kidney disease [standard mortality ratio (SMR) = 1.76, 95 % confidence interval (CI) 1.01-2.86] was observed by Olsen et al (2012) in an epidemiological study of 2,650 participants.…”
Section: Introductionmentioning
confidence: 98%